The impact of Treasure Hunt games in enhancing basic Japanese vocabulary retention and student motivation through gamified learning - Hussin, Sanimah; Abdullah, Muhammad Alif Redzuan (HRMARS, 2024)
This study examines the impact of Treasure Hunt games on improving students' retention of basic Japanese vocabulary and motivation through gamified learning. The study addresses a central problem in language learning: the difficulty of retaining vocabulary when using traditional memorization techniques, which often fail to engage students and lead to inconsistent results. To overcome this challenge, treasure hunt games were investigated as a fun learning strategy that encourages interactivity and practical application. A quasi-experimental design was implemented with an experimental group that used a treasure hunt game for vocabulary learning and a control group that relied on traditional memorization methods. Analyzing the results before and after the test showed that the experimental group experienced a 20% improvement in vocabulary retention, which was significantly higher than the 8% improvement of the control group. In addition, a motivational questionnaire based on Self-Determination Theory (SDT) revealed that students in the experimental group reported higher levels of autonomy, competence, and relatedness, indicating greater engagement and motivation compared to the control group. The study aims to investigate whether game-based learning offers a more engaging and effective approach to vocabulary teaching and overcomes the limitations of traditional methods. The results suggest that Treasure Hunt games improve both vocabulary memorization and student motivation, creating a more inclusive and engaging learning environment. The implication of this study emphasizes the potential of game-based learning to improve both cognitive and motivational outcomes in language learning. Future studies are recommended to investigate the long-term effects of game-based interventions and their impact on other language skills, such as grammar and syntax, in different educational contexts.